Answer:
x = -2
Step-by-step explanation:
since y is common in both equations, you can equate them to be equal
-2x² - 4x + 5 = 2x² + 4x + 5
4x² + 8x = 0
factor out 4x
4x(x + 2) = 0
divide both sides by 4x
x + 2 = 0
x = -2
Answer:
x = 4
Step-by-step explanation:
2 + 3(3x - 6) = 5(x - 3) + 15
Expand the parenthesis:
2 + 9x - 18 = 5x - 15 + 15
Simplify:
9x - 16 = 5x
Subtract 5x from both sides:
4x - 16 = 0
Add 16 to both sides:
4x = 16
Divide both sides by 4:
x = 4
The scatterplot shows how many miles Marissa jogged over 10 days. Which statements are true? Check all that apply.
Marissa jogged 5 miles on the first day.
Marissa jogged 6 miles on the second day.
Marissa jogged 9 miles on the third day.
Marissa jogged 3 miles on the fourth day.
Marissa jogged 3 miles on the ninth day.vvvvvThe scatterplot shows how many miles Marissa jogged over 10 days. Which statements are true? Check all that apply.
Marissa jogged 5 miles on the first day.
Marissa jogged 6 miles on the second day.
Marissa jogged 9 miles on the third day.
Marissa jogged 3 miles on the fourth day.
Marissa jogged 3 miles on the ninth day.Answer:
Step-by-step explanation:
tthe